E-Government : an exploratory study of online government procurement / Maniam Kaliannan - Kaliannan, Maniam (Research Management Institute (RMI), 2008)
The quest to improve the government service delivery is becoming an important agenda for most governments. The introduction oflCT in the public sector especially E-Government initiatives opens up a new chapter in the government administration throughout the world. Governments have deployed ICT to serve their citizens in an efficient and effective manner. This paper presents an empirical investigation of Malaysian government's e-Procurement initiative (locally known as e-Perolehan). The aim of the paper is to examine factors that influence the current and future use of the system within the supplier community. These factors are grouped in three perspectives, (i) organizational perspective; (ii) technological perspective; and (Hi) environmental perspective. The general consensus amongst both the buyer and seller communities is that e-procurement will become an important management tool to enhance the performance of supply chain especially in the public sector. However, before this occurs, the findings suggest that several issues must be addressed by the relevant authorities in light of the three perspectives as mentioned above, to improve the procurement process at the federal government level.